ANALYSIS ON FACTORS THAT AFFECT STOCK PRICE WITH DIVIDEND POLICY AS MODERATING VARIABLE - Semarjaya, Diwei Lico; Sufiyati, Sufiyati (International Journal of Application on Economics and Business, 2024)
This study aims to determine the impact of Current Ratio, Return on Assets, Price Earnings Ratio, Earnings per Share and Net Profit Margin on stock price in consumer non cyclicals companies listed on the Indonesia Stock Exchange for period 2020-2022 and using dividend policy as moderating variable. The sampling technique was purposive sampling and the data that met the criteria were 49 data from 18 companies which were processed using Statistical Package for the Social Science (SPSS) vers 26.0. The result of this study Current Ratio, Price Earnings Ratio and Earnings per Share significantly influences the stock price, while Return on Assets and Net Profit Margin have no significant effect on stock price. Dividend Policy as a moderating variable unable to moderate the Current Ratio, Return on Assets, Price Earnings Ratio, Earnings per Share and Net Profit Margin on Stock Price.